2006
DOI: 10.1186/1744-8603-2-3
|View full text |Cite
|
Sign up to set email alerts
|

The developing world in The New England Journal of Medicine

Abstract: Background: Rampant disease in poor countries impedes development and contributes to growing North-South disparities; however, leading international medical journals underreport on health research priorities for developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…A previous review, published in the New England Journal of Medicine between 1997 and 2004, reported less than 3% of research-addressed health issues in the developing world, and the majority of this addressed communicable diseases including HIV 23. A further review reported that >90% of published research by scientists comes from just 20 countries 24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous review, published in the New England Journal of Medicine between 1997 and 2004, reported less than 3% of research-addressed health issues in the developing world, and the majority of this addressed communicable diseases including HIV 23. A further review reported that >90% of published research by scientists comes from just 20 countries 24.…”
Section: Discussionmentioning
confidence: 99%
“…But the medical information gap between rich and poor countries appears to be larger than the gap in funding for research 23. Commercial efforts are too often focused on where the money is—in providing end products to health professionals 30.…”
Section: Implication For Practice and Researchmentioning
confidence: 99%
“…A study by Lown & Banerjee to assess the New England Journal of Medicine's coverage of health issues of the developing world, found that in 416 weekly issues over an eight-year period < 3% of articles were devoted to such issues. 18 Other studies have shown similar evidence of systematic bias by medical journals from developed countries against highlighting diseases of poverty, and recent reports have documented the problem of neglected tropical diseases. 19,20 Overcoming the limitations The statement and recommendations of the Budapest Open Access Initiative on which all subsequent open access developments are based, is concerned with free public access to peer reviewed publicly-funded research publications.…”
Section: Solutionsmentioning
confidence: 75%
“…Poverty reduction strategy papers, as mentioned within Labonte and Torgerson’s framework [2], were evident, with a focus on the conceptualisation of aid [12] and on alignment of spending and domestic priorities [13]. The development of research was a topic within this; authors focused upon under-representation of low-income countries in the literature, research partnerships and ethical standards of research [1416]. Sustainability of global and local initiatives were also covered [17], as was the concept of ‘reverse innovation’ [18].…”
Section: Resultsmentioning
confidence: 99%